A MISCARRIAGE OF JUSTICE: Racial Discrimination in Ava Du Vernay's Television Series When They See Us (2019) - Tiara Richna Rumata, - (2021)
Racial discrimination is still happening up until recent days. This research investigates the phenomena in a series entitled When They See Us (2019) by Ava DuVernay, which retells a story of the injustice experienced by five Black teenagers. This study aims to identify the types of discrimination experienced by the main characters and how these acts are portrayed. The researcher uses the theory of racial discrimination proposed by Pincus (1996) and Heintz and Stracey's (2006) theory of film to uncover the types and the portrayal of racial discrimination experienced by the main characters. The dialogue and the scenes were analyzed using textual analysis. The three types of racial discrimination (individual, institutional, and structural discrimination) were found in the data. The discrimination acts are a systemic practice, and the three types of discrimination are interrelated. The portrayal of the acts is also explored using the mise en scene and cinematography by analyzing the scene containing the discrimination to see how the acts are depicted and emphasized in the series. The series helps to give an insight into how the Black people experienced the discrimination done by the authorities. Thus, this study explores the notion of racial discrimination against minority groups by showcasing discrimination done by authorities and experienced by Black teenagers.